Poseganje v slovstveno folkloro - Stanonik, Marija (Traditiones (Ljubljana), 2006)
This article systematically opens a discussion on a very neglected areas of Slovenian misical and literary folklore: the re-creation of Slovenian literary folklore. Until recently, literary history has addressed this issue with judgments of questions of morals and signs of weak poetic power. Likewise, in line with the principles of transcription as reproduction, literary and musical folklore have in principle rejected any kind of intervention in the text and have not been prepared to engage with the spirit and circumstances of a time that influenced certain Slovenian authors in their decision to reshape folk songs.
Keywords: ethnology; etnologija; slovstvena folkloristika; ljudsko slovstvo; oral literature; ljudske pesmi; Ethnopoetics; history of literature; literarna zgodovina